A Poisoned Gift? The Hireability Signals of an Income-Support Program for the Senior Unemployed - Axana Dalle; Philippe Sterkens; Stijn Baert (Institute of Labor Economics (IZA), 2023)
Many OECD countries invest heavily in labour-market programs to prolong careers. Although active labour-market programs designed for this purpose have frequently been evaluated, less is known about the employment impact of more passive regimes that make labour-market participation later in life feasible. This study focuses on the latter by investigating the hiring opportunities of senior job candidates who partake in a system that ensures older labour-market participants a company supplement in addition to unemployment benefits when they are dismissed. Therefore, we conduct a state-of-the-art scenario experiment in which 360 genuine recruiters evaluate fictitious job candidates who have spent varying durations unemployed in regimes with and without the company supplement. Because they evaluate candidates with respect to both hireability and productivity perceptions, we can identify the mechanisms at play. Overall, we find no evidence of employer-side stigma hindering the re-employment of older unemployed in the program. On the contrary, the longer-term unemployed even benefit – in terms of hiring chances – from partaking in this regime because it seemingly mitigates the regular stigmatisation of long-term unemployment, especially for men. More concretely, recruiters judge the long-term unemployed more mildly, especially with respect to perceived flexibility, when they receive the company supplement and still apply.
Keywords: J71; J32; J14; 330; hiring discrimination; signalling effect; income support; labour market program; vignettes